Virtual Extimacy and Conjugality: Possible Repercussions - Campos, Carolina Mendes (2020)
This study aimed to investigate the possible repercussions of “virtual extimacy” in the experience of conjugality today. The notion of intimacy has undergone significant transformations. Historically, intimacy had a strong connection with the idea of privacy. However, today, the transformation of intimacy is remarkable, since the shared information has reached visibility never before imagined. The notion of “virtual extimacy” was constructed to designate this new perspective of intimacy in the internet space. Six married people who were also users of the Facebook social network were interviewed. The interviews were analyzed using the content analysis method. The categories of analysis emerged from these narratives. With these analyses, it was verified that we are facing not a dichotomous phenomenon that separates the virtual from the real, but rather a novelty that joins and intertwines the threads of experience with the other inside and outside the internet.